Physiological analysis of severe chlamydia psittaci pneumonia and clinical diagnosis after doxycycline-based treatment - He, Lujuan; Yang, Hongzhong; Liu, Shenggang; Liang, Weijun; Zhou, Zezhi; Long, Jing; Wu, Jinyang (Frontiers in Physiology, 2023)
Objective: To describe the clinical spectrum of severe Chlamydia psittaci pneumonia in order to understand the disease better. Methods: Retrospective analysis was made on 31 patients with severe Chlamydia psittaci pneumonia diagnosed in ICU by next-generation sequencing of metagenome Metagenomic next-generation sequencing(mNGS) from January 2019–November 2022, including clinical characteristics, laboratory examination results, imaging characteristics, treatment, and prognosis. Results: We included 31 patients with severe Chlamydia psittaci pneumonia, 15 of whom had a history of virus exposure. There were 12 cases with multiple bacterial infections, and the common symptoms included fever (31/31,100%), dyspnea (31/31, 100%), cough (22/31, 71.0%), and myalgia (20/31, 64.5%). Laboratory data showed that white blood cells were average or slightly increased, but the levels of C-reactive protein and neutrophils were high. CT findings of the lung were consolidation (19/31, 61.3%) and pleural effusion (11/31, 35.5%). Only one lobe was involved in 11 patients (35.5%). Before diagnosis, 22 patients (71.0%) did not have atypical pathogens in their antimicrobial regimen. After diagnosis, 19 patients (61.3%) received single drug treatment, of which doxycycline or moxifloxacin were the most commonly used drugs. Among 31 patients, three died, nine improved, and nineteen were cured. Conclusion: The clinical manifestations of severe Chlamydia psittaci pneumonia are non-specific. The application of mNGS can improve the diagnostic accuracy of Chlamydia psittaci pneumonia, reduce the unnecessary use of antibiotics, and shorten the course of the disease. Doxycycline-based treatment is effective for severe chlamydia psittaci pneumonia, but it is necessary to understand the secondary bacterial infection and other complications in the course of the disease.